Некоторые проблемы защиты права собственности при применении мер уголовно-процессуального принуждения - Kirillova, Nataliya (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The aim of the study is to evaluate the relation between right to property and the criminal procedure compulsions. The author presents the selected issues of the property right protection law system in the context of the criminal proceeding.
Selected issues of the property right protection in the scope of criminal procedure compulsions
Keywords: property right protection; civil law; criminal procedure